2014
DOI: 10.1007/s11357-014-9683-7
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in cardiovascular system, autonomic functions, and levels of BDNF of healthy active males: role of yogic practice

Abstract: Aging is associated with decline in cardiovascular, autonomic function, and brain-derived neurotropic factor (BDNF). Reports are scanty regarding whether yoga can improve age-related degenerative changes in healthy active men. This study is designed to appraise the role of yoga in improving age-related degenerative changes in cardiometabolic risk profile, autonomic function, stress, and BDNF. Healthy active males of three age groups (20-29, 30-39, and 40-49 years) were randomly assigned to practice yoga daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 53 publications
4
85
1
1
Order By: Relevance
“…Like physical activity, yoga has been found to have beneficial impacts on neurological and physiological activity and behavior in a range of populations. The reported benefits of yoga include increased slow-frequency brain wave activity (Arambula et al, 2001); favorable profiles on heart rate (HR) variability, depression, perceived stress, and superior aerobic fitness (Satin, Linden & Millman, 2014); and significant decrement of cortisol and increment in brain-derived neurotropic factor (BDNF), serotonin, and dopamine (Pal et al, 2014). In essence, the practice of yoga exercise elicits reduced activation of the sympathetic nervous system and increased activation of the parasympathetic nervous system resulting in a sense of equilibrium into the body and mind, and increased emotional self-regulation (Streeter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Like physical activity, yoga has been found to have beneficial impacts on neurological and physiological activity and behavior in a range of populations. The reported benefits of yoga include increased slow-frequency brain wave activity (Arambula et al, 2001); favorable profiles on heart rate (HR) variability, depression, perceived stress, and superior aerobic fitness (Satin, Linden & Millman, 2014); and significant decrement of cortisol and increment in brain-derived neurotropic factor (BDNF), serotonin, and dopamine (Pal et al, 2014). In essence, the practice of yoga exercise elicits reduced activation of the sympathetic nervous system and increased activation of the parasympathetic nervous system resulting in a sense of equilibrium into the body and mind, and increased emotional self-regulation (Streeter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to explore the practice of regular yoga as one of the strategies for the treating anxiety-and depression-related disorders. Furthermore, another study revealed that yogic practice daily for 1 h for a period of 3 months helps in lowering ACTH and cortisol, while elevating serotonin, dopamine, and BDNF in healthy active men [76] .…”
Section: Effect Of Yoga On Neurotransmittersmentioning
confidence: 98%
“…The main cardiovascular system changes during aging decreased heart rate and adrenergic modulation of cardiac function [19]. While (Pal et al, [20] said that changes in rhythm of the heart places the aging population at increased risk.…”
Section: Cardiac Function Changes and Agementioning
confidence: 99%
“…The veins walls also thickened with age due to an increased in deposition of connective tissue and calcium leading to development of veins varicoses. Due to veins blood pressure was low these alterations are not significant for function of CVS but may be of performing a role in the occurrence of phlebitis and formation of thrombus [20]. cardiovascular homeostasis may be affected by age through increased velocity of pulse wave and ejection time prolongation enhancing summation of arterial waves either antegrade or retrograde, leading to to increase of both pulse and systolic blood pressures in aging.…”
Section: Dysfunction Of Endotheliummentioning
confidence: 99%